Simultaneous Treatment of Organic (Phenol) and Heavy Metal (Cr6+ or Pt4+) Wastes over TiO2, ZnO-TiO2 and CdS-TiO2 Photocatalysts - Slamet, Slamet; Arbianti, R.; Daryanto, Daryanto (UI Scholars Hub, 2005)
Simultaneous Treatment of Organic (Phenol) and Heavy Metal (Cr6+ or Pt4+) Wastes over TiO2, ZnO-TiO2 and CdS-TiO2 Photocatalysts. Treatment of heavy metal (Cr6+ and Pt4+) and organic (phenol) wastes has been studied using the relatively new method, i.e. simultaneous photocatalytic process over TiO2 photocatalysts in the batch photoreactor. Following the photocatalytic reduction of the heavy metal wastes, recovery of Cr and Pt was carried out by precipitation and leaching method, respectively. The experimental results show that in the simultaneous photocatalytic system, there is a synergism effect between the photocatalytic reduction of heavy metal waste (Cr6+ or Pt4+) and the oxidation of organic waste (phenol), so that increasing the conversion of each other. Dopant of ZnO with the optimum loading (0.5 wt%) could slightly increase the performance of TiO2 photocatalyst in photocatalytic treatment of the wastes. Whereas CdS dopant with the optimum loading of 1 wt% could significantly enhance the performance of TiO2 photocatalyst in simultaneous Cr(VI) reduction and phenol oxidation with the highest conversion of ≥ 97 % and 93 %, respectively. Photocatalytic reduction of Pt(IV) under 0.5%ZnO-TiO2 and 1%CdS-TiO2 photocatalysts effectively occurred with a high conversion (> 99 %) in 2 hours irradiation of UV. The optimum precipitation condition of Cr(III) recovery was achieved at pH = 9, with the efficiency of recovery was 91 %. Optimum temperature of leaching process in Pt recovery was 100 oC, with the efficiency of recovery was 86 %.